Prevalence and correlates of childhood obesity in suburban area of Odisha: A cross sectional study (Epidemiology, Biostatistics, and Public Health, 2022)
Introduction: In India obesity and overweight is increasing among urban adolescents. Both under and over nutrition is grappling the country at faster rate. Present study was an attempt to explore obesity and overweight prevalence among school going children in suburban areas of Cuttack city, Odisha, India and their correlates.Methodology: A cross-sectional study was done among school children in suburban area of Cuttack city, Odisha. A predesigned and pretested questionnaire was used to interview the study participants to elicit information about their age, number of siblings, birth order of the child, working status of parents, television screen viewing time, mode of transport to school and dietary habit of the students. A total of 550 children studying in class five to ten participated in our study.Result: Out of 550 children screened, nearly (14) 2.5% students were thin or severely thin, whereas (67)12.1% students were overweight or obese. Univariate analysis revealed that girls were almost five times at higher risk of being overweight/obesity compared to boys (OR: 4.78 95%CI: 1.35-16.93). Children who used motorized vehicles for going to school had an unadjusted Odds ratio of 10.08 [95%CI: 2.08-48.77] of being overweight or obese compared to those who walked to school. Having more than one child at home (OR= 0.15, 95%CI: 0.039-0.6) and doing physical activity for more than 30min per day (0.105, 95%CI: 0.015-0.72) were found to be protective against overweight and obesity.Conclusion: Bearing in mind the burden of overweight and obesity among school children there is a need for periodic screening, awareness at school and parent counselling.
Keywords: Overweight; obesity; prevalence; risk factors; Odisha; India